A Sensitive Assay System To Test Antisense Oligonucleotides for Splice Suppression Therapy in the Mouse Liver - Lorena Gallego-Villar; Hiu Man Viecelli; Belén Pérez; Cary O Harding; Magdalena Ugarte; Beat Thöny; Lourdes R Desviat (Elsevier, 2014)
We have previously demonstrated the efficacy of antisense therapy for splicing defects in cellular models of metabolic diseases, suppressing the use of cryptic splice sites or pseudoexon insertions. To date, no animal models with these defects are available. Here, we propose exon skipping of the phenylalanine hydroxylase (Pah) gene expressed in liver and kidney to generate systemic hyperphenylalaninemia in mice as a sensitive in vivo assay to test splice suppression. Systemic elevation of blood L-Phe can be quantified using tandem MS/MS. Exon 11 and/or 12 skipping for the normal PAH gene was validated in hepatoma cells for comparing two oligonucleotide chemistries, morpholinos and locked nucleic acids. Subsequently, Vivo-morpholinos (VMO) were tested in wild-type and in phenotypically normal Pahenu2/+ heterozygous mice to target exon 11 and/or 12 of the murine Pah gene using different VMO dosing, mode of injection and treatment regimes. Consecutive intravenous injections of VMO resulted in transient hyperphenylalaninemia correlating with complete exon skipping and absence of PAH protein and enzyme activity. Sustained effect required repeated injection of VMOs. Our results provide not only a sensitive in vivo assay to test for splice-modulating antisense oligonucleotides, but also a simple method to generate murine models for genetic liver diseases.